Abdominal obesity in Malaysian adults: National Health and Morbidity Survey III (NHMS III, 2006) - Kee, Chee Cheong; Haniff, Jamaiyah; Mohammad Nor, Noor Safiza; Appannah, Geeta; Khor, Geok Lin; Shahar, Suzana; Ab Rahman, Jamalludin; Rasat, Rahmah; Zainuddin, Ahmad Ali; Abd Talib, Ruzita; Wong, N. F.; Yusoff, Ahmad Faudzi (Nutrition Society of Malaysia, 2008)
Abdominal obesity (AO) is an independent risk factor for cardiovascular disease, hypertension and diabetes mellitus in adults. There is a lack of data on the magnitude and socio-demographic profile of AO among Malaysian adults at the national level. In the Third National Health and Morbidity Survey (NHMS III) conducted in 2006, AO of adults aged 18 years and above was determined based on the waist circumference as part of the nutritional status assessment. This article reports the prevalence of AO in relation to socio-economic factors and demographic characteristics of adult subjects. Out of a total of 33,465 eligible individuals 18 years and above, waist circumference was measured in 32,900 (98.3%) individuals. The prevalence of AO was assessed using the cut-off points recommended by World Health Organization. The mean waist circumference in men and women was 84.0cm [95% confidence interval (95% CI): 83.8, 84.3] and 80.3cm (95% CI: 80.1, 80.6) respectively. The national prevalence of AO was 17.4% (95% CI: 16.9, 17.9). The identified risks of AO were women (OR: 4.2, 95% CI: 3.8, 4.6), aged 50-59 years (OR: 5.6, 95% CI: 4.0, 7.7), Indians (OR: 3.0, 95% CI: 2.4, 3.8), housewives (OR: 1.4, 95% CI: 1.1, 1.7), subjects with primary education (OR: 1.3, 95% CI: 1.1, 1.5) and ever married (OR: 1.4, 95% CI: 1.2, 1.6). Being the largest population-based study on AO among Malaysians, these findings have important public health implications. There is an urgent need to revise public health policies and programmes aimed at prevention of abdominal obesity especially in the groups at risk.